CONTEXTUAL COHERENCE IN RECOUNT ESSAY - Wienny Ardriyati; Heny Hartono (Celt: A Journal of Culture, English Language Teaching & Literature, 2004)
Writing is one of the most difficult aspects in language skills. In fact. for some learners writing could be the most difficult skill compared to other language skills. This skill requires precise grammar; appropriate uses of cohesive devices. capability to choose the most suitable vocabulary. and the ability to maintain the coherence. Maintaining the coherence. especially the contextual coherence in recount essays is not easy. Learners often have problems with the use of cohesive devices. grammatical structures. and the schematic structure of a recount. In fact. those three problems are the components that support contextual coherence. When there are problems in those components. contextual coherence cannot be achieved.